(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
There are several ways to understand the Buddhist perspective on women’s status in society.Examining how the position of women in religious and secular life in India evolved before to and after theadvent of Buddhism might help determine the extent to which the Buddha’s teachings caused a dramatictransformation in society. If the Buddha’s teaching accords women a different position than men, asmany other faiths do, it will be fascinating to see how this plays out. It is feasible to investigate if aperson’s predetermined gender affects how far down the Buddha’s path they go. In order to avoidskipping even the slightest suggestion of the royal ladies in the Jataka stories, we have attempted toinclude all pertinent episodes and subject matter